Repositioning Zakat Distribution for Modern Social Harms: Empowering Victims of Online Gambling through Advocacy and Asnaf Alignment - Muliansyah, Eko (Lafadz Jaya Publisher, 2025)
The rise of online gambling in Indonesia has created a new category of socio-economic victims—those facing financial collapse, psychological trauma, and social exclusion. This study explores how zakat distribution can be repositioned to address such digital-era harms by reinterpreting classical asnaf categories, particularly gharimin and fakir-miskin, through the lens of maqāṣid al-sharī‘ah. Using a normative-empirical approach, this research integrates doctrinal analysis with stakeholder perceptions gathered through focus group discussions and policy reviews. Findings indicate strong public and scholarly support for more inclusive zakat allocation. While institutional conservatism persists, over 78% of public respondents support zakat for victims of online gambling when linked to rehabilitation and empowerment. This study argues that zakat must evolve from a static legal obligation into a dynamic tool for digital justice—supporting not only economic recovery but also mental resilience and social reintegration. By aligning zakat governance with ethical imperatives and sustainable development goals, zakat institutions can restore their prophetic role in protecting vulnerable communities. The repositioning of zakat is both a theological necessity and a policy innovation in an age where poverty is often entangled with digital exploitation.